External Group Labeling of Objects in 2D Medical Images Using Spring-Mass Model - Tarek, Muhammad Masud; Ferdosi, Bilkis Jamal (British Journal of Healthcare and Medical Research, 2018)
The parallel processing of verbal elements like textual labels, annotations etc. with non-verbal i.e. visual elements, provides maximum integration of human mind. Textual labels and annotations aid in understanding medical data visualization. But it is a very challenging task to generate hand-made like illustration labels in an automated system. The paper presents a noble approach for dynamic external labeling of segmented 2D computer tomography (CT) slices. Various efficient algorithms are approached to solve labeling problems in modular form. The system emphasizes on the readability and clarity of labels while generating dynamic group labels in real time for 2D slices using external labeling layout.